PENGARUH FAKTOR NON KEUANGAN TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Zulfikar, Muslim; Syafruddin, Muchamad (Diponegoro Journal of Accounting, 2013)
This study aims to examine and to provide empirical evidence of the influence of the auditor reputation, auditor client tenure, mandatory disclosure, company size, and previous year audit opinion on the provision of going-concern opinion.Â At this time, auditor starts to be requested of his responsibility to disclose the entityâ€™s going concern, not only detecting fraud in the financial statement but also predicting the company capability to maintain company going concern. Populations of this research is manufacturing companies listed at Indonesian Stock Exchange (IDX) between 2008 to 2011. Research sample amounts to 68 companies selected with purposive sampling method, with observation period of 4 years. The method that been used to analyses the correlation between variable are logistic regression method. Logistic regression is used becauseÂ the dependent variable is binary in which the observed outcome can have only two possible types (going concern opinion vs non going concern opinion). From the result, can be concluded that company size have no effect on the provision of going-concern opinion. On the other hand, auditor reputation, auditor client tenure, mandatory disclosure and previous year audit opinion affect to the provision of going concern opinion.